Структурные и морфологические характеристики пористых материалов TiNi-Ti-Co - Кафтаранова, Мария Ивановна (Перспективы развития фундаментальных наук. Т. 1 : сборник научных трудов XIX Международной конференции студентов, аспирантов и молодых ученых, 26-29 апреля 2022 г.)
The transition-chemical composition of TiNi–Ti-Co alloys has been studied. The possibility of adjusting the atomic composition of TiNi by introducing Ti from 5 to 10 at. % and the use of Co in crime 0.6 at.%. Structural-reciprocal and morphological features of TiNi–Ti-Co alloys obtained by diffusion sintering with characteristic transformation temperatures have been studied.